Classification of acoustic emission signals registered during the foam drainage process - RANACHOWSKI, Z.; RANACHOWSKI, P. (Archives of Acoustics, 1997)
This article refers to the changes of spectral features of Acoustic Emission (AE) signal. The AE signal is generated during drainage process concerning a foam made of detergent solution. The subroutines to extract the AE events and its spectral features from the real AE signal recordings are described. The effectiveness of classifying procedures based on two linear and one nonlinear algorithms used to recognition different AE patterns is also discussed.